ANALISA HUKUM EKONOMI TERHADAP STANDARISASI MUTU PRODUK DALAM PERLINDUNGAN KONSUMEN DI INDONESIA - Wiwik Sri Widiarty (to-ra, 2017)
In the current era of globalization of the world economy, the situation of regulation of the circulation of goods and / or services becomes increasingly tight. In order to maintain the quality of quality products, to maintain a competitive product must meet the Indonesian National Standard (SNI), namely through Government Regulation No. 102 of 2000 on National Standardization, and International Standardization. While the National Standardization of Quality is the Standardization made by the Government, and implemented sectorally. Consumer users of goods and / or services purchased products must meet health, safety, security and environmental standards (K3L), and for business actors themselves do not understand the meaning of quality certification of goods issued by authorized agencies / bodies, so because of ignorance this is very detrimental to the Consumer as stipulated in Law No. 8 of 1999 on Consumer Protection. Kata Kunci: Standarisasi Mutu Produk, Perlindungan Konsumen